2015
DOI: 10.1186/s40623-015-0362-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequency distributions of magnetic storms and SI+SSC-derived records at Kakioka, Memambetsu, and Kanoya

Abstract: The Japan Meteorological Agency keeps records of geomagnetic phenomena observed at Kakioka (magnetic latitude, 27.47°), Memambetsu (magnetic latitude, 35.44°), and Kanoya (magnetic latitude, 22.00°). We used these records to examine the cumulative frequency distribution of magnetic storms, sudden impulses, and storm sudden commencements. The distributions of magnetic storms resemble the Gutenberg-Richter relation between earthquake frequency and magnitude used in seismology. The coefficients determined with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The frequency 14.1 Hz may be a resonance frequency of Mg 2+ in some conditions [226]. On the other hand, the fundamental frequencies of the Schumann resonance are represented by 7.8 Hz, 14.1 Hz, 20.3 Hz, 26.4 Hz, and 32.5 Hz [285] and fall within the frequency ranges of theta (4-7 Hz), alpha (7-12 Hz), sigma (12-14 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-80 Hz) rhythms of human brain electrical activity [63,[286][287][288][289][290][291]. A high similarity of the human EEG profile to low Schumann resonance frequencies has been described.…”
Section: Potential Mechanisms Of Action Of Magnetic Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency 14.1 Hz may be a resonance frequency of Mg 2+ in some conditions [226]. On the other hand, the fundamental frequencies of the Schumann resonance are represented by 7.8 Hz, 14.1 Hz, 20.3 Hz, 26.4 Hz, and 32.5 Hz [285] and fall within the frequency ranges of theta (4-7 Hz), alpha (7-12 Hz), sigma (12-14 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-80 Hz) rhythms of human brain electrical activity [63,[286][287][288][289][290][291]. A high similarity of the human EEG profile to low Schumann resonance frequencies has been described.…”
Section: Potential Mechanisms Of Action Of Magnetic Fieldsmentioning
confidence: 99%
“…The first and most "obvious" range lies in the frequency and induction limits f (50-60 Hz) and corresponds to industrial MFs. Formally, this range can be divided into two parts: strong ELF-MF effects f (10-300)B(>10 µT) industrial frequencies and their harmonics and subharmonics (fields with such induction are rarely encountered in everyday life and are used in laboratory experiments, for example, to test theories about cyclotron resonances (Figure 7b (1)) [27,28,261]; weak MFs (<10 µT) of the same frequency range are often encountered in everyday life. In addition, in everyday life, we are surrounded by urban background MFs mainly consisting of noise from electrical equipment, transportation, etc.…”
Section: Dependence Of Quantitative Characteristics Of Biological Eff...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, acknowledging an advantage of Japan's long-term monitoring effort of geomagnetic activities at Kakioka Magnetic Observatory (KAK), their complied event lists of magnetic storms and SCs are used for the statistics to estimate the possible amplitudes of the 100-year and 1000-year events. Using the KAK lists, the possible power-law distributions of the amplitude of magnetic storms as well as SCs were discussed by Minamoto et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Next, three papers deal with statistical studies of the magnetospheric disturbances. Nakamura et al (2015) study the auroral electrojets, and Minamoto et al (2015) address the magnetic storms and SCs observed by the Kakioka Magnetic Observatory. The frequencies of occurrence of severe space weather are useful not only to the scientists but also to society.…”
mentioning
confidence: 99%